CREATING A NATIONAL PARK GEOGRAPHIC INFORMATION SYSTEM: A CASE STUDY FOR THE MOUNT IDA - Gulgen, F.; Basaraner, M.; Yucel, M. A.; Cetinkaya, S. (BULGARIAN CARTOGRAPHIC ASSOC, 2014)
Geographic information systems are essential tools for planning, monitoring, management and sustainable use of resources of national parks. In this study, we present a case study for national park geographic information system for the Mount Ida. For this purpose, topographic maps at 1:25000 scale, GPS-based trekking and climbing routes, campgrounds and other thematic information (flora, fauna, preserved areas, promenade places, forests, biodiversity, campgrounds etc.) and CORINE data obtained from the Turkish National Park Service have been used. Feature and attribute catalogue has been created for the national park with focus on nature-based tourism and outdoor recreation. As a result, national park geographic information system will help carry out national park services efficiently.
Keywords: GIS; Geography